Breast conserving surgery versus mastectomy: overall and relative survival—a population based study by the Danish Breast Cancer Cooperative Group (DBCG). (2nd January 2018) - Christiansen, Peer; Carstensen, Stina Lyck; Ejlertsen, Bent; Kroman, Niels; Offersen, Birgitte; Bodilsen, Anne; Jensen, Maj-Britt
Abstract: Background: Observational studies have pointed at a better survival after breast conserving surgery (BCS) compared with mastectomy. The aim of the present study was to evaluate whether this remains true when more extensive tumor characteristics and treatment data were included. Methods: The cohort included patients registered after primary surgery for early invasive breast cancer in the database of the Danish Breast Cancer Cooperative Group, in the period 1995–2012. The cohort was divided into three groups: (i) patients who primarily had a mastectomy, (ii) patients treated by BCS, and (iii) patients who primarily had BCS and then mastectomy [intention to treat (ITT) by BCS]. The association between overall mortality and standard mortality ratio (SMR) and risk factors was analyzed in univariate and multivariate Poisson regression models. Results: A total of 58, 331 patients were included: 27, 143 in the mastectomy group, 26, 958 in the BCS group, and 4230 in the BCS-ITT group. After adjusting for patient and treatment characteristics, the relative risk (RR) was 1.20 (95% CI: 1.15–1.25) after mastectomy and 1.08 (95% CI: 1.01–1.15) after BCS first and then mastectomy, as compared to BCS. Statistically significant interactions were not observed for age, period of treatment, and nodal status, but patients with Charlson's Comorbidity Index (CCI) score 2+ had no increased mortality after mastectomy, as opposed to patients with CCI 0–1. Loco-regional radiation therapy (RT) in node positive patients did not reduce the increased risk associated with mastectomy [RR = 1.28 (95% CI 1.19–1.38)]. Conclusion: Patients assigned to BCS have a better survival than patients assigned to mastectomy. Residual confounding after adjustment for registered characteristics presumably explained the different outcomes, thus consistent with selection bias. Diversities in RT did not appear to explain the observed difference in survival after BCS and mastectomy.